scRNA-Seq reveals age-dependent microglial evolution as a determinant of immune response following spinal cord injury - Lufei Shao; Yueliang Chang; Jinfang Liu; Leilei Lin; Long Chang; Jialin Zhang; Zhibin Lan; Honglai Zhang; Xiaolei Chen (Brain Research Bulletin)
Spinal cord injury (SCI) is a debilitating condition of the central nervous system (CNS) that leads to severe impairments in sensory and motor functions. Previous studies have pointed out that patient age is a critical factor influencing SCI prognosis. However, the role of microglia in age-related differences in SCI outcomes remains unclear. The current study aims to identify specific microglial subtypes and investigate their responses and functional differences in SCI recovery across different age groups. Single-cell RNA sequencing (scRNA-seq) data were obtained from the Gene Expression Omnibus (GEO) database, integrating multiple datasets to identify microglial subtypes. We performed pseudotime trajectory analysis and cell-cell communication analysis to understand microglial differentiation and interactions. Finally, immunofluorescence staining of mouse model samples was conducted to validate our bioinformatics findings. Microglia were classified into four subtypes: Homeostatic, Proliferating, Inflammatory A, and Inflammatory B. The Young SCI group exhibited a higher proportion of Homeostatic microglia and Inflammatory microglia A, whereas the old SCI group had more Inflammatory Microglia B but lacked Homeostatic Microglia. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses revealed that markers for homeostasis microglia were enriched in immune modulation pathways. While makers for Inflammatory Microglia were enriched in immune response pathways. Specifically, markers for Inflammatory microglia B were enriched in pathways associated with overactive immune response. Pseudotime analysis indicated that microglia in young mice predominantly differentiated into Inflammatory Microglia A and Homeostatic Microglia, whereas in old mice, they tended to only differentiate into Inflammatory Microglia B. CellChat analysis showed increased pro-inflammatory signaling generated by Inflammatory Microglia B, exclusively in the old group. Our study demonstrates significant differences in microglial subtypes and functions between different age groups following SCI. These findings provide novel insights into the development of age-related therapeutic strategies and microglia-targeted biological treatments for SCI.